Linking data from a large clinical trial with the Australian Cerebral Palsy Register. (8th May 2020) - Shepherd, Emily; Mcintyre, Sarah; Smithers‐Sheedy, Hayley; Ashwood, Pat; Sullivan, Thomas R; te Velde, Anna; Doyle, Lex W; Makrides, Maria; Middleton, Philippa; Crowther, Caroline A
Abstract : Aim: To link data from a large maternal perinatal trial with the Australian Cerebral Palsy Register (ACPR) to identify children with cerebral palsy (CP). Method: Deidentified data from the Australasian Collaborative Trial of Magnesium Sulphate (ACTOMgSO4 ) and the ACPR were linked. Children born from 1996 to 2000 at Australian hospitals who survived and had 2‐year paediatric assessments were included. Children identified with CP in: (1) both the ACTOMgSO4 (2y) and the ACPR (5y), (2) the ACTOMgSO4 only, and (3) the ACPR only were compared. Results: We included 913 children (492 males, 421 females; mean gestational age at birth 27.8wks [standard deviation 2.1wks]; range 23.0–40.0wks). Eighty‐four children received a CP diagnosis: 35 by the ACTOMgSO4 and the ACPR, 29 by the ACTOMgSO4 only, and 20 by the ACPR only. The ACTOMgSO4 diagnosed 76.2% (95% confidence interval [CI] 65.9–84.1) and the ACPR identified 65.5% (95% CI 54.7–74.9). Children born in states/territories with long‐standing versus more recently established registers were more likely to be included on the ACPR ( p <0.05). Interpretation: Linking deidentified perinatal trial data with the ACPR was achieved. Limitations of both strategies for identifying children with CP in this era (late 1990s and early 2000s) probably explain many of the differences observed, and inform future linkage studies and evaluations of CP‐preventive interventions. What this paper adds: Randomized trial data were linked with the Australian Cerebral Palsy Register. Trial (2y) and register (up to 5y) diagnoses of cerebral palsy (CP) differed. States with long‐standing registers were more likely to include children with CP. What this paper adds: Randomized trial data were linked with the Australian Cerebral Palsy Register. Trial (2y) and register (up to 5y) diagnoses of cerebral palsy (CP) differed. States with long‐standing registers were more likely to include children with CP. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This original article is commented on by Adams‐Chapman on page 1116 of this issue. Vinculación de datos de un gran estudio clínico con el Registro Australiano de Parálisis Cerebral: Objetivo: Vincular los datos de un gran estudio perinatal materno con el Registro Australiano de Parálisis Cerebral (ACPR) para identificar a niños con parálisis cerebral (PC). Método: Se identificaron datos no identificados del Ensayo de colaboración australiano de sulfato de magnesio (ACTOMgSO4) y el ACPR. Se incluyeron niños nacidos entre 1996 y 2000 en hospitales australianos que sobrevivieron y tuvieron evaluaciones pediátricas de 2 años. Los niños identificados con PC en: (1) tanto el ACTOMgSO4 (2y) como el ACPR (5y), (2) solo el ACTOMgSO4 y (3) solo se compararon el ACPR. Resultados: Se incluyeron 913 niños (492 varones, 421 mujeres; edad gestacional media al nacer 27.8 semanas [desviación estándar 2.1 semanas]; rango 23.0–40.0 semanas). Ochenta y cuatro niños recibieron un diagnóstico de PC: 35 por ACTOMgSO4 y ACPR, 29 solo por ACTOMgSO4 y 20 solo por ACPR. El ACTOMgSO4 diagnosticó el 76, 2% (intervalo de confianza [IC] del 95%: 65, 9‐84, 1) y el ACPR identificó el 65, 5% (IC del 95%: 54, 7‐74, 9). Los niños nacidos en estados / territorios con registros de larga data versus registros establecidos más recientemente tenían más probabilidades de ser incluidos en el ACPR (p <0.05). Interpretación: Se logró vincular los datos de estudios perinatales desidentificados con el ACPR. Las limitaciones de ambas estrategias para identificar a los niños con PC en esta época (finales de los 90 y principios de los 2000) probablemente explican muchas de las diferencias observadas e informan futuros estudios de vinculación y evaluaciones de intervenciones preventivas de la PC. Ligando dados de um grande estudo clínico com o Registro Australiano de Paralisia Cerebral: Objetivo: Ligar os dados de um grande estudo maternal perinatal com o Registro Australiano de Paralisia Cerebral (RAPC) para identificar crianças com paralisia cerebral (PC). Método: Dados não identificados do Estudo Australasiano Colaborativo sobre Sulfato de Magnésio (ACTOMgSO4 ) e da RAPC foram relacionados. Crianças nascidas entre 1996 e 2000 em hospitais australianos que sobreviveram e tiveram avaliações pediátricas de 2 anos foram incluídas. Crianças identificadas com PC em: (1) tanto no ACTOMgSO4 (2anos) quanto no RAPC (5anos), (2) apenas no ACTOMgSO4, e (3) apenas no RAPC foram comparados. Resultados: Incluímos 913 crianças (492 do sexo masculino, 421 do sexo feminino; idade gestacional média ao nascimento de 27, 8 semanas [desvio padrão 2, 1semanas]; variação 23, 0–40, 0 semanas). Oitenta e quarto crianças receberam diagnóstico de PC: 35 no ACTOMgSO4 e RAPC, 29 apenas no ACTOMgSO4, e 20 pelo RAPC apenas. O ACTOMgSO4 diagnosticou 76, 2% (intervalo de confiança a 95% [IC] 65, 9–84, 1) e o RAPC identificou 65, 5% (IC 95% 54, 7–74, 9). Crianças nascidas em estados/territórios com registros bem estabelecidos versus aqueles mais recentes tiveram maior probabilidade de ser incluídas no RAPC ( p <0, 05). Interpretação: Foi possível ligar dados não identificados perinatais com a RAPC. Limitações de ambas as estratégias para identificar crianças com PC neste período (final dos anos 90 e início dos anos 2000) provavelmente explicam muitas das diferenças observadas, e informam futuros estudos de ligação e avaliações de intervenções.